Aberrant Left Subclavian Artery Arising from the Main Pulmonary Artery with Different Associations : A Case Series - Biswas, Prodip Kumar; Dasgupta, Saikat; Chowdhury, Naharuma Ivy Haider; Al Manzoo, Md Ishtiaque Syed; Azad, Md A K; Islam, Shahidul; Shamsuddin, Md AK; Sharifuzzaman, Md (Journal of Chittagong Medical College Teachers’ Association, 2023)
Anomalous Left Subclavian Artery (ALSA) is a congenital anomaly, in which the left subclavian artery arises from the Main Pulmonary Artery (MPA). Patients may remain asymptomatic and may be later diagnosed either at autopsy or incidentally during angiographic studies for associated cardiac defects. The surgical management of such defect is not clearly defined. We hereby present a case series of three patients we have treated from July 2015 to January 2021, who were diagnosed incidentally during the routine investigation and treated accordingly. JCMCTA 2023 ; 34 (1) : 138-144